Dose response rate of garlic for the control of Haemonchus contortus in merino wethers and the subsequent sensory quality of the meat - Strickland, Victoria Judith (Curtin University, 2011)
Haemonchus contortus is a gastrointestinal nematode of significant importance in Australia and worldwide. It prevails in tropical zones, summer rainfall regions and mostly coastal areas in temperate regions. The high fecundity of the female parasite and its ability to persist in sheep for extended periods of time has helped in this parasite’s development of resistance to multiple synthetic anthelmintics.The development of parasite anthelmintic resistance has been influenced by producers’ over-reliance on these chemicals to control parasites as well as poor management practices such as under-dosing. With the increased occurrence of multiple drug resistant parasites, other more sustainable methods are being investigated, including the use of medicinal plant extracts with anthelmintic properties, such as garlic. The subsequent meat quality of the animals after being fed these herbal concoctions to control parasites is not often investigated. The aims of this thesis were to investigate the use of garlic to control the gastrointestinal nematode H. contortus and then evaluate the subsequent meat quality by consumer taste panel.To look at garlic for the control of H. contortus a 14-week feeding trial was conducted over the summer of 2008. The trial used thirty nine Merino wether lambs in five groups fed a high quality basal ration and infected with 4000 L3 “Kirby” H. contortus larvae. The treatment groups consisted of an untreated negative control group, a positive control group treated with abamectin 28 days post infection and three treatment groups fed 0.9%, 1.8% and 3.6% garlic (included into the basal ration).There was no reduction in worm egg counts between the negative control and the garlic treatment groups. There was however a significant interaction between the effects of the treatments and VFI on WEC. The 3.6% garlic treatment group had significantly lower final liveweight, weight gain, and feed conversion efficiencies than the 0.9% and 1.8% garlic treatment groups.The tenderloins collected from all animals at slaughter at the end of the feeding trial were used in a consumer taste panel to assess the subsequent meat quality. The meat samples were assessed by 104 untrained participants in a blind tasting. Participants were asked to asses the meat samples of flavour, acceptability as well as an optional comment section. Participants rated the flavour of the meat from the garlic and control lambs the same. The 3.6% garlic treatment had a significantly higher percentage of “yes” responses for the panellists’ assessment of “acceptability as lamb”. The 3.6% garlic also had a significantly higher percentage of positive comments about the samples, suggesting that this lamb was more acceptable than the meat from the control animals.The results from these experiments suggest that fresh garlic included in a pelleted ration does not show potential to aid in the control of H. contortus and may have negative effects on production if fed at a rate of 3.6%. However the inclusion of garlic in a pelleted ration improved the acceptability of lamb as assessed by consumers, so there may be the potential for a niche product.